Distribution Patterns And Diversity of Meso-Zooplankton with Special Reference to Icthyoplankton in cochin Estuary - Anakha (Dept.of Aquatic Environement Mangement, 2017)
Abstract- Samples were collected from 17 stations from North end to south end of the estuary. Salinity showed a maximum value near to the estuarine zone and a minimum near the lake zone. Bio-volume of zooplankton in the pre-monsoon season showed a maximum value compared to the monsoon and post-monsoon. A total of 22 groups of zooplankton and a group of fish juveniles and decapod juveniles were recorded from the sampling. The groups recorded are Copepoda, Decapod larvae, Gastropoda, Megalopa of crab, Zoea of crab, Lucifer, Mysid, Protozoea, Fish eggs, Fish larvae, Polychaeta, Chaetognatha, Amphipoda, Jelly fish, Cladocera, Cyprea larvae, Ostracoda, Stomatopoda, Oligochaeta, Oikopleura, Ctenophora and Bivalvia. The copepods are the most dominant group observed from all the stations. The family of fish larvae observed are Gobiidae, Engraulidae, Clupidae, Polynemidae, Siganidae, Scombridae, Ambassidae,Mugilidae, Cyanoglossidae and Soleidae. The most dominant family observed is Gobiidae. More diversity of fish larvae are observed in the middle and south zone of the estuary.